IMPLIKASI PERBEDAAN PARADIGMA TERHADAP PENANGANAN PENGUNGSI, PENCARI SUAKA, DAN MIGRAN ILEGAL: TANTANGAN DAN SOLUSI - Pratama, Reza Akbar; Hilmy, Muhadzib Rezki; Berlian, Theresya (Jurnal Ilmiah Kajian Keimigrasian, 2024)
The background of this research is the increase in global migration triggered by various factors such as armed conflict, political instability, and natural disasters. This has led to an increase in the number of refugees, asylum seekers, and illegal migrants that require proper handling. The purpose of this study is to analyse the different definitions, challenges, and impacts of the three migrant groups on receiving countries, as well as to offer more coherent and effective policy solutions. The research method used is desk research with a qualitative descriptive approach, which involves analysing secondary data from various literatures, including international policies and case studies from migration destination countries. The research data includes reports from international agencies such as UNHCR and IOM, as well as statistical data related to migration. The results show that there is significant legal uncertainty in the handling of these three groups, which results in an increased economic and social burden on receiving countries. In addition, political and social tensions also often arise due to inconsistent immigration policies. The conclusion of this study emphasises the need for more humane and human rights-focused immigration policy reforms, as well as enhanced international cooperation in addressing global migration.